2017
DOI: 10.1093/mnras/stx2967
|View full text |Cite
|
Sign up to set email alerts
|

Flickering AGN can explain the strong circumgalactic O viobserved by COS-Halos

Abstract: Proximity zone fossils (PZFs) are ionization signatures around recently active galactic nuclei (AGN) where metal species in the circumgalactic medium remain overionized after the AGN has shut-off due to their long recombination timescales. We explore cosmological zoom hydrodynamic simulations using the EAGLE model paired with a non-equilibrium ionization and cooling module including time-variable AGN radiation to model PZFs around star-forming, disk galaxies in the z ∼ 0.2 Universe. Previous simulations typica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
88
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 96 publications
(92 citation statements)
references
References 79 publications
3
88
1
Order By: Relevance
“…For less massive galaxies, the virial temperature would be too cool for strong O VI presence, whereas the virial temperature would be too high for group environments as a large fraction of O VI is ionized out to higher ionization species. Nelson et al (2018) found similar trends in the O VI column density with halo mass, but attributed them to black hole feedback (also see Oppenheimer et al 2018). Several other works have also shown this trend in both observations (Bielby et al 2019;Zahedy et al 2019) and with gaseous halo models (Qu & Bregman 2018).…”
Section: Introductionmentioning
confidence: 76%
“…For less massive galaxies, the virial temperature would be too cool for strong O VI presence, whereas the virial temperature would be too high for group environments as a large fraction of O VI is ionized out to higher ionization species. Nelson et al (2018) found similar trends in the O VI column density with halo mass, but attributed them to black hole feedback (also see Oppenheimer et al 2018). Several other works have also shown this trend in both observations (Bielby et al 2019;Zahedy et al 2019) and with gaseous halo models (Qu & Bregman 2018).…”
Section: Introductionmentioning
confidence: 76%
“…Peeples et al 2018;Hummels et al 2018). Incorporating AGN feedback has improved predictions of high-ion abundances, but simulations still struggle to reproduce low-ion abundances, even for hydrogen (Oppenheimer et al 2018). If low-ion CGM clouds do form on scales < 500 pc as our analysis and that of others suggests, then the resolution of CGM gas in simulations must increase by orders of magnitude in order to reflect the hydrodynamics on relevant scales (Marinacci et al 2010;Crighton et al 2015;McCourt et al 2018;Liang & Remming 2018;Sparre et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…There could be actively star-forming galaxies or relatively faint AGNs in close proximity to the absorber, below the magnitude limit of SDSS spectroscopic survey. Also, as Segers et al (2017) and Oppenheimer et al (2017) have proposed, galaxies with past AGN activity in time scales shorter than the recombination time scales of high ions (t 10 6 yrs) can have enhanced O vi ionization fractions in their haloes. We cannot dismiss such a scenario.…”
Section: Ionization Modelingmentioning
confidence: 90%